Can you use a coconut to find groundwater?. Issue 1 (1st December 2019) - Costall, Alex; Teo, Bryce; Pethick, Andrew
Summary: Divining has been used for centuries for groundwater and mineral prospecting. Historically, divining has been reliant on a rod, or pair of rods, accompanied by a particular individual. Recently, the use of fluid-bearing containers was cited as a viable water divining technique by a popular Indian 'youtuber'. We numerically simulate the response from a coconut using an appropriate robust statistical method, similar to that deployed by the diviner in their videos. Coincidentally, a clear response in the rotation of the coconut is generated wherever the diviner desires. Our results indicate that divining is and remains at the whim of the practitioner. Unfortunately, this pseudo-science pervades in the modern day and discredits other methods of remote subsurface imaging.